Tsuchihashi, Paul Yachita S. J., Japanese Chronological Tables from 601 to 1871 a. D., Sophia University Press, Tokio, 1952. (Monumenta Nipponica Monographs, núm. 11.) 128 pp. - F., C. (Estudios de Asia y África, 1969)
-